Human Amnion Epithelial Cells Produce Soluble Factors that Enhance Liver Repair by Reducing Fibrosis While Maintaining Regeneration in a Model of Chronic Liver Injury. (18th August 2020) - Hodge, Alexander; Andrewartha, Neil; Lourensz, Dinushka; Strauss, Robyn; Correia, Jeanne; Goonetilleke, Mihiri; Yeoh, George; Lim, Rebecca; Sievert, William
Human amnion epithelial cells (hAECs) exert potent antifibrotic and anti-inflammatory effects when transplanted into preclinical models of tissue fibrosis. These effects are mediated in part via the secretion of soluble factors by hAECs which modulate signaling pathways and affect cell types involved in inflammation and fibrosis. Based on these reports, we hypothesized that these soluble factors may also support liver regeneration during chronic liver injury. To test this, we characterized the effect of both hAECs and hAEC-conditioned medium (CM) on liver repair in a mouse model of carbon tetrachloride (CCl4 )-induced fibrosis. Liver repair was assessed by liver fibrosis, hepatocyte proliferation, and the liver progenitor cell (LPC) response. We found that the administration of hAECs or hAEC-CM reduced liver injury and fibrosis, sustained hepatocyte proliferation, and reduced LPC numbers during chronic liver injury. Additionally, we undertook in vitro studies to document both the cell–cell and paracrine-mediated effects of hAECs on LPCs by investigating the effects of co-culturing the LPCs and hAECs and hAEC-CM on LPCs. We found little change in LPCs co-cultured with hAECs. In contrast, hAEC-CM enhances LPC proliferation and differentiation. These findings suggest that paracrine factors secreted by hAECs enhance liver repair by reducing fibrosis while promoting regeneration during chronic liver injury.